Upaya Kepala Sekolah Dalam Mengembangkan Kompetensi Pedagogik Guru Studi Kasus di SMAN Jembrana Bali - Rohil Zilfa (Darajat: Jurnal Pendidikan Agama Islam, 2020)
The problem of the quality of educators is an important discussion in the advancement of the world of education. This can be seen from the unequal quality of educators in each education unit. Especially the pedagogical competence of teachers. The development of pedagogic competencies of educators in educational institutions is a must, considering that educators are active resources in learning. While the principal as a leader who has a function as a manager has a strategic role in empowering educators in schools, so that teachers have the competencies that have been determined in the National Education Standards. Based on these problems, the focus of this research is: The principal's strategy in developing pedagogical competence of educators in State Senior High School 1 Negara Bali. This type of research is qualitative research with a single case study type i, because this research has a subject background in one scene; in State Senior High School 1. Data sourced from documentation and informants determined by snowball sampling. Data collection techniques using interviews, observation and documentation study. Data analysis by reducing data, presenting data then drawing conclusions. Data validity was checked by source triangulation. This research resulted in the following: The principal's strategy in developing the pedagogic competence of educators in State Senior High School 1, in terms of the pedagogical competences studied included: First, Mastering learning theory and the principles of educational learning by 1. Following Technical Guidance and Training , 2. Socializing the principles of learning. Second, developing a curriculum related to the subject being taught through 1. Teacher organization, 2. Forming a Curriculum Development Team, 3. Supervising. Third, make use of information and communication technology in learning that is taught through workshops